Students’ Satisfaction with Interactive Forms of Training with Elements of Gamification - S. Demchenko, Tatiana; V. Vinichenko, Mikhail; V. Demchenko, Maksim; Y. Ilina, Irina; V. Buley, Natalya; V. Duplij, Elena (International Journal of Engineering and Technology, 2018)
The article considers students' satisfaction with interactive forms of training with elements of gamification. Based on the empirical study, the level of students’ satisfaction with interactive forms of training with elements of gamification has been measured. The study has been conducted at 6 educational organizations that carry out educational activities on educational programs of higher education – bachelor, specialist and master degree programs. A set of sociological methods has been used in the study: a questionnaire survey of students, an expert survey of teachers working at higher education institutions, an analysis of documents; content analysis; a method of mathematical data processing (correlation analysis, using the software package SPSS Statistics 23). Based on the analysis of the scientific literature and the results of the sociological research conducted, it has been established that the students are more satisfied with the quality of interactive sessions with elements of gamification (57.01%) than with the quality of training by traditional methods (23.36%) and the quality of the content of classes conducted by traditional methods (19.63%). It has been revealed that the use of interactive forms of training with elements of gamification is the most effective: to increase the effectiveness of mastering the training material (20%); for decision-making (17.33%); to heighten interest in learning (15.33%). The closeness of the views of students and teachers on the assessment of interactive forms of training with elements of gamification and assessment of classes conducted by traditional methods has been determined by means of Spearman's rank correlation coefficient. The obtained data of the correlation analysis have shown a rather high level of correlation and indicated the closeness of the views of students and teachers on the phenomena studied.
Keywords: Classes; Higher education institution (HEI); Interactivity; Gamification; Satisfaction; Students.